Ultra-broadband FeNi3/NiZnFe2O4/ZnO composite powders for microwave absorption - S. Golchinvafa; S.M. Masoudpanah; S. Alamolhoda (Journal of Materials Research and Technology, 2022)
FeNi3/NiZnFe2O4/ZnO composite powders were in-situ prepared for microwave absorption by solution combustion synthesis method in a closed system. The effects of fuel content and composition on the structural, microstructural, and magnetic and microwave absorption properties were studied by X-ray diffractometry, scanning electron microscopy, vibrating sample magnetometry, and vector network analyzer techniques. There were FeNi3, NiZnFe2O4 and ZnO phases in the samples obtained at higher fuel contents and higher amounts of Zn2+ substitution. The synthesized powders had porous and spongy microstructure in which the porosity and particle size decreased with the fuel contents. The values of permittivity and permeability decreased with Zn2+ addition. By controlling over the amounts of fuel and substituted Zn2+ species, the values of saturation magnetization and the coercivity were tuned in the range of 30–70 emu/g and 153–131 Oe, respectively. The composite sample containing NiZnFe2O4-34 wt.% FeNi3-8 wt. % ZnO exhibited a minimum reflection loss of −40 dB and an effective absorption bandwidth of 4.6 GHz in Ku band at the matching thickness of 1.5 mm. The NiZnFe2O4-17 wt.% FeNi3-32 wt. % ZnO composite powders had the broader effective absorption bandwidth of 6.7 GHz at the matching thickness of 2.3 mm, but with the minimum reflection loss of −24 dB at a matching frequency of 16.5 GHz.